KOMUNIKASI PENDIDIK DAN PESERTA DIDIK DALAM PENDIDIKAN ISLAM - Abdul Aziz (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2017)
The expert agreed about the importance of communicating in education studies. Education studies department needs communication for liven up the class and learning atmoshave here as a dialogical mechanism, not only mechanism. The problem is the teacher as a central point in learning activities didn’t have aby skill to liven up the class atmosphere. They often failed liven up the class effectively because they failed in communicating. The communicating ability of teachers is an urgent aspect. The communication problem in education studies is not about important or not important, but it is about how the teacher in class create communication effectively. The effective communication’s learning in education studies need two way communication. Teachers and students must havethe same ability to communicate well. This article will explain deep review about the communiation between teachers and students in the islamic perspective.